Attachment of Histidine Tags to Recombinant Tumor Necrosis Factor-Alpha Drastically Changes Its Properties - Irena Fonda; Maja Kenig; Vladka Gaberc-Porekar; Primo Pristovaek; Viktor Menart (The Scientific World Journal, 2002)
When studying two different histidine tags attached to the N-termini of the trimeric cytokine tumor necrosis factor alpha (TNF), the biological activity — measured as cytotoxicity on the L-929 cell line — of both tagged proteins was drastically reduced. The longer His10 tag reduced cytotoxicity to approximately 16% and the shorter His7 tag to 6% of the activity of their nontagged counterparts. After removal of the tags, biological activities reverted to the expected normal values, which clearly shows the key role of the attached histidine tags in diminishing biological activity. Studies on the mechanism of these effects revealed no specific interactions and showed that even the natural flexible N-terminus of TNF presents a steric hindrance for receptor binding, while any extension of the N-terminus increases this hindrance and consequently reduces biological activity. Also, in other proteins, the ligand or substrate binding sites may be hindered by histidine tags, leading to wrong conclusions about biological activity or other properties of the proteins. Thus caution is advised when using His-tagged proteins directly in screening procedures or in research.